Why does Indra drink soma in so many different ways? A study of synonymic compounds in the R̥gveda and of the interaction of poetry and grammar (Atti del Sodalizio Glottologico Milanese, 2017)
The presence of many synonimical derivatives from the Vedic root pā- “drink” is thoroughly examined according to their compositional, metrical and stylistic features. KEYWORDS: Vedic, soma, drink, compounds, synonyms,